2006 International Conference on Mathematical Methods in Electromagnetic Theory
DOI: 10.1109/mmet.2006.1689838
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Wave Diffraction on a Resistive Cone with Longitudinal Slots

Abstract: A problem of exciting a resistive cone with longitudinal periodical slots by a magnetic radial dipole is considered. Resistive sheet boundary conditions are used for simulating inhomogeneous curve linear surface properties (cone curvature is taken into account). The solution method is based on applying the Kontorovich-Lebedev integral transforms and a semi-inversion method. Special impedance effects are studied by analyzing analytical solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…The validity of version (5)? (6) is justified for some concrete problems and obtained results correspond to known physical concepts. The third difkulty which came up in solution of such type of theoretical problems is connected with the multiconical surface consisting of cones with different electrical properties or different boundary conditions including conditions in the singular points.…”
supporting
confidence: 60%
See 1 more Smart Citation
“…The validity of version (5)? (6) is justified for some concrete problems and obtained results correspond to known physical concepts. The third difkulty which came up in solution of such type of theoretical problems is connected with the multiconical surface consisting of cones with different electrical properties or different boundary conditions including conditions in the singular points.…”
supporting
confidence: 60%
“…It corresponds to the residue around the pole v = 1/2 [l]. It can be shown that T-wave due to residue around the pole v = -1/2 corresponds to joined wires or joined center and then should be used formulae (5), (6). The fact of more strong singularity in the vertex of radial conducting conic surface in contrary to isotropic perfectly conducting cone is substantiated by results of [6] where the conic structure with radial slots is considered.…”
mentioning
confidence: 99%